Contrasting patterns of transposable element insertions in Drosophila heat-shock promoters. - Haney, R.A.; Feder, M.E. (PLoS ONE, 2009)
The proximal promoter regions of heat-shock genes harbor a remarkable number of P transposable element (TE) insertions relative to both positive and negative control proximal promoter regions in natural populations of Drosophila melanogaster. We have screened the sequenced genomes of 12 species of Drosophila to test whether this pattern is unique to these populations. In the 12 species' genomes, transposable element insertions are no more abundant in promoter regions of single-copy heat-shock genes than in promoters with similar or dissimilar architecture. Also, insertions appear randomly distributed across the promoter region, whereas insertions clustered near the transcription start site in promoters of single-copy heat-shock genes in D. melanogaster natural populations. Hsp70 promoters exhibit more TE insertions per promoter than all other genesets in the 12 species, similarly to in natural populations of D. melanogaster. Insertions in the Hsp70 promoter region, however, cluster away from the transcription start site in the 12 species, but near it in natural populations of D. melanogaster. These results suggest that D. melanogaster heat-shock promoters are unique in terms of their interaction with transposable elements, and confirm that Hsp70 promoters are distinctive in TE insertions across Drosophila.